Safety of Anticancer Agents Used in Children: A Focus on Their Off-Label Use Through Data From the Spontaneous Reporting System - Mascolo, Annamaria; Scavone, Cristina; Bertini, Michele; Brusco, Simona; Punzo, Francesca; Pota, Elvira; Di Martino, Martina; Di Pinto, Daniela; Rossi, Francesca (Frontiers in Pharmacology, 2020)
Background: Among factors influencing the higher risk of developing unknown or rare adverse drug reactions (ADRs) among children and adolescents, there is the frequent off-label use of drugs that seems to be very common in pediatric oncological patients. Our study aim to collect and evaluate data on the safety profile of antineoplastic drugs and their off-label use in the pediatrics population using real life data. Methods: We retrieved Individual Case Safety Reports (ICSRs) with an anticancer agent as suspected drug among those reported through the Campania spontaneous reporting system from 1 January 2013 to 30 September 2019. We classified ICSRs into four off-label categories: “age”, “route of administration”, “weight”, and “therapeutic indication”. We defined an ICSR as an off-label case if it met at least one of the aforementioned categories for at least one of the reported suspected antineoplastic drugs. Results: A total of 18 ICSRs (7.6%) out of 236 were classified as off-label cases. The median age of patients was 13 years (interquartile range, IQR: 6 - 16), with 94.4% of cases occurring in male patients. In the classification of the off-label category, 16 ICSRs were categorized according to the “therapeutic indication” and 2 for the “age”. No case was categorized for the off-label categories “route of administration” and “weight”. The 2 off-label cases categorized as “age” were both related to the use of brentuximab vedotin for Hodgkin's lymphoma in patients aged 16 years. Twenty-nine ADRs (1.6 suspected adverse drug reactions per ICSR) were identified among off-label cases. Among ADRs, those reported more than one were diarrhea (N=3), neutropenia (N=3), nausea (N=2), pyrexia (N=2), and vomit (N=2). Conclusions: Our findings showed a low number of ICSRs classified as off-label. The majority of off-label ICSRs were categorized for the “therapeutic indication. This low number of off-label ICSRs might be largely due to the underreporting phenomenon, which is a major limit in pharmacovigilance. Therefore, we believe that spreading pharmacovigilance knowledge and awareness might improve this aspect.